2019
DOI: 10.1111/echo.14487
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity in breast cancer treatment: What about left ventricular diastolic function and left atrial function?

Abstract: Aims Cardiotoxicity is a possible complication of cancer treatment, particularly with anthracyclines and anti‐HER2 drugs. Systolic dysfunction has already been described. Diastolic dysfunction and left atrial function are less studied. We sought to analyze the impact of cardiotoxic treatments on left ventricular diastolic function and left atrial (LA) function. Methods and Results Retrospective study of 100 patients (all women, with a mean age of 54 ± 12 years) with three exams in the span of 1 year during tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
3
18
2
Order By: Relevance
“…A longer follow-up period will be necessary to establish the clinical outcomes of these patients, but DD abnormalities over time are associated with subsequent systolic dysfunction and cardiotoxicity. 7 It was also possible to observe that patients with baseline DD are less associated with reduced LVEF than those who develop DD throughout treatment, suggesting that baseline DD is not associated with subsequent systolic dysfunction, similarly to what Timóteo et al 16 and Upshaw et al 7 reported when following patients for 12 months and 6.5 years, respectively.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…A longer follow-up period will be necessary to establish the clinical outcomes of these patients, but DD abnormalities over time are associated with subsequent systolic dysfunction and cardiotoxicity. 7 It was also possible to observe that patients with baseline DD are less associated with reduced LVEF than those who develop DD throughout treatment, suggesting that baseline DD is not associated with subsequent systolic dysfunction, similarly to what Timóteo et al 16 and Upshaw et al 7 reported when following patients for 12 months and 6.5 years, respectively.…”
Section: Discussionsupporting
confidence: 54%
“…19 In turn, variations in the E/e' parameter are also linked to chronic conditions, 13,20 which justifies the absence of changes in both parameters in the present study. Timóteo et al 16 showed significant indexed LA volume changes, but not until later -on 12-month echocardiography follow-up.…”
Section: Barroso Et Al Early Diastolic Dysfunction After Chemotherapymentioning
confidence: 91%
“…Ana Teresa Timóteo et al suggested that no significant change in LA strain in breast cancer patients was observed after chemotherapy. 6 In contrast, Hyukjin Park et al suggested that a significant decline in LA strain developed after chemotherapy for breast cancer. 7 The respective changes in LASr, LAScd, and LASct in these patients is still a matter of debate.…”
Section: Introductionmentioning
confidence: 98%
“…Although the peak global longitudinal and radial strain decreased, 10 patients demonstrated a reduction in lateral S' at 3 months after trastuzumab treatment, and these 10 patients all eventually developed trastuzumab-mediated cardiotoxicity. Retrospective studies have also shown that 20% of patients develop new or worsening diastolic dysfunction during breast cancer treatment (42,43). In the aforementioned studies, the diastolic dysfunction was evaluated by TDI indexes including mitral annular e'velocity (septal and lateral) and average E/e' ratio.…”
Section: Surveillance Strategiesmentioning
confidence: 99%